Technological innovation in services and the efficiency of Malaysian Commercial Banks - Chee, Wooi Hooy; Sok, Gee Chan (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper revisits relative fficiency of commercial banks in Malaysia using Data Envelopment Analysis (or.a) over the 2004-2012 periods. We take into account technological innovation in bankservices, a new dimension thatwere not investigated by any previous literature. Our mainfindings are: (l) Commercial banks in Malaysian have higher pure technical fficient as compare to scale fficient. (2) Foreign banks are relatively inefficient but the gap has been gradually closing after the end of the capital control by the Malaysian government in 2005. (3) Excess numbers of Branches, Cash Deposit Machine and Cheque Deposit Machine appeared to be the major weakness of the infficiency banl<sO. ur result implies technologicali nnovation in bank servicesi s one important dimensioni n addressingt he relative fficiency of commercial bqnl$. Banlcs that provide better technological services do acquire competitive advantage against their peers.